The gut microbiota of insects – diversity in structure and function. Issue 5 (17th June 2013) - Engel, Philipp; Moran, Nancy A.
Abstract: Insect guts present distinctive environments for microbial colonization, and bacteria in the gut potentially provide many beneficial services to their hosts. Insects display a wide range in degree of dependence on gut bacteria for basic functions. Most insect guts contain relatively few microbial species as compared to mammalian guts, but some insects harbor large gut communities of specialized bacteria. Others are colonized only opportunistically and sparsely by bacteria common in other environments. Insect digestive tracts vary extensively in morphology and physicochemical properties, factors that greatly influence microbial community structure. One obstacle to the evolution of intimate associations with gut microorganisms is the lack of dependable transmission routes between host individuals. Here, social insects, such as termites, ants, and bees, are exceptions: social interactions provide opportunities for transfer of gut bacteria, and some of the most distinctive and consistent gut communities, with specialized beneficial functions in nutrition and protection, have been found in social insect species. Still, gut bacteria of other insects have also been shown to contribute to nutrition, protection from parasites and pathogens, modulation of immune responses, and communication. The extent of these roles is still unclear and awaits further studies. Abstract : Different insect groups are host to a broad diversity of gut microbial communities, which vary in complexity, extent of adaptation to the host gut environment, and roles in host ecology and function.